STACEY STEELE and KATHRYN TAYLOR (eds.) Legal Education in Asia: Globalization, Change and Contexts - Nottage, Luke (Zeitschrift für Japanisches Recht, 2010)
STACEY STEELE and KATHRYN TAYLOR (eds.) Legal Education in Asia: Globalization, Change and Contexts Routledge (London, 2010) ISBN 978-0-415-49433-5; xviii + 330 pp; GBP 155 / EUR 121,99